SISTEMATISASI DAN KEMANASUKAAN BAHASA SEBAGAI MEDIA KOMUNIKASI - Djuli, Labu; Bustan, Fransiskus; Fernandez, Sebastianus; Ludji, Arni Djenita; Nahdliyah, Nur Laili (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
This paper discusses systematization and arbitrariness as characteristics of language as a means of communication in the life of a society as members of a speech community. The materials are based on secondary data collected through library research. The characteristics of systematization are concerned with the significances of language as a system because language has a set of rules as the frames of reference for a speech community when communicating with each other. The set of rules, as reflected in phonology, morphology, syntax and semantics, make the system of one language differ from those of other languages. The characteristics of arbitrariness are concerned with relationship of two poles of linguistic sign, involving forms or signifieds and meanings or signifiers, which are based on social conventions inherited from previous generations. The characteristics of arbitrariness are beneficial to the study of both linguistics and semiotics in which language is defined as a system of sign.